“Pre-service teachers´ perceptions about communicative language teaching (clt) in English classes” - Paltán Vásconez, Marlon Fabricio (2022)
Communicative language teaching (CLT), emphasizes the interaction between students to develop oral communication. CLT has been implemented in some English classrooms providing students motivation, self-confidence and collaborative work in the learning process. Some studies demonstrate that the CLT is an approach that has helped to develop student’s communication and social interaction between them appropriately. Despite these benefits, in Ecuador there is little research on pre-service teachers ‘perceptions about the communicative language teaching (CLT) in English classes. Thus, it was decided to explore the pre-service English teachers’ perceptions since it would let them realize how much they know about the CLT approach and how they can use it in their English classes. Whereby, this research aimed at identifying pre-service teachers´ perceptions about Communicative Language Teaching (CLT) in English classes. The mixed method was used; both the qualitative and quantitative approach with a deductive methodology. For the data collection process researchers carried out a survey technique which contained 3 open questions and 13 open closed questions. Participants were 73 EFL pre-service teachers: 18 from the eighth semester and 55 from the seventh semester. The criteria to select the participants was homogeneous sampling and convenience sampling so participants were selected considering those who did their pre-service teaching practices. The analysis of the data indicated that most participants have knowledge about CLT and also, they sometimes, often and usually apply CLT approach in their pre-service practices. The activities most frequently used by them in their English classes were games, role plays, discussion and pair or group work activities. Likewise, they also considered that students prefer activities, such as role play and games rather than others. Moreover, as part of the results, participants were in favor of employing more CLT activities in their practices because it allows learners to lose fear while they speak as well as to enhance their oral communication in the target language. It is suggested that these perceptions should be taken into account by pre-service teachers in order to make use of CLT in their future English classes.